2021
DOI: 10.1136/bmjopen-2021-057362
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of a multicentre cluster randomised control trial to investigate the clinical and cost-effectiveness of a structured diagnostic pathway in primary care for chronic breathlessness: protocol paper

Abstract: IntroductionChronic breathlessness is a common and debilitating symptom, associated with high healthcare use and reduced quality of life. Challenges and delays in diagnosis for people with chronic breathlessness frequently occur, leading to delayed access to therapies. The overarching hypothesis is a symptom-based approach to diagnosis in primary care would lead to earlier diagnosis, and therefore earlier treatment and improved longer-term outcomes including health-related quality of life. This study aims to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Semi-structured interviews were conducted between November 2019 and October 2021 with participants enrolled in a mixed-method feasibility cluster randomised controlled trial (cRCT) in England called Breathlessness DiagnosE Early in Primary care (Breathe DEEP) (ISRCTN14483247). 29 The Breathe DEEP trial involved 10 GP practices across Leicester and Leicestershire, which were cluster randomised to either a structured diagnostic pathway (intervention) or to usual care. The structured diagnostic pathway included a panel of investigations, completed within 2 months of consultation with the GP for breathlessness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-structured interviews were conducted between November 2019 and October 2021 with participants enrolled in a mixed-method feasibility cluster randomised controlled trial (cRCT) in England called Breathlessness DiagnosE Early in Primary care (Breathe DEEP) (ISRCTN14483247). 29 The Breathe DEEP trial involved 10 GP practices across Leicester and Leicestershire, which were cluster randomised to either a structured diagnostic pathway (intervention) or to usual care. The structured diagnostic pathway included a panel of investigations, completed within 2 months of consultation with the GP for breathlessness.…”
Section: Methodsmentioning
confidence: 99%
“…30 Eligible patients were >40 years old, breathless for longer than 2 months, and presenting for the first time, with no previous diagnoses for their breathlessness. 29 Semi-structured interviews were conducted with clinicians from 10 practices enrolled in the cRCT, who were not necessarily directly involved in the care of the patients interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…The ageing population and its burden on health-care systems warrant early detection of patients at risk of functional decline and mortality. [40]. Forty-eight patients were included in ten GP practices.…”
Section: Additional Presentationsmentioning
confidence: 99%
“…Finally, G. Doe and co-workers (Leicester, UK) presented a feasibility study investigating the impact of a structured diagnostic pathway designed to confirm or exclude the five most common causes of chronic breathlessness in patients over 40 years old: COPD, anxiety, anaemia, heart failure and obesity/deconditioning [ 40 , 41 ]. 48 patients were included from 10 GP practices [ 41 ].…”
Section: Group 103: General Practice and Primary Carementioning
confidence: 99%
“…The first method (Strategy 1) for a primary care breathlessness cohort study used weekly searches for new breathlessness Read codes in the electronic patient record (EPR), followed by a mail out of study information to identified patients at 14 GP practices. The second method (Strategy 2) implemented an opportunist approach using an electronic template on the EPR, triggered at the point of consultation by either breathlessness-free text or Read codes at 10 GP practices 8 . The template (Fig.…”
Section: Recruitment Strategies and Participantsmentioning
confidence: 99%